Central and peripheral hemodynamics in pre-pathologic and pathologic diagnostics among swimmers - Feroya, E. V. (The Russian Journal of Physical Education and Sport, 2018)
In terms of the volume and intensity increase of the training and competitive loads the demands claimed on athletes` blood circulation apparatus also increased. Blood circulation apparatus provides athletes` high working capacity and is the most important limiting factor in the system of oxygen transfer. Materials. The main hemodynamic parameters complex study at central and peripheral levels. Methods. Information sources analysis and summarizing, Doppler sonography, tetrapolar chest rheography methods, rheohepatography, rheoencephalography and peripheral rheovasography, methods of mathematical statistics. Results. According to the received results, an important factor in pathogenesis of chronic overtension of athletes` myocardium is circulatory injuries. It should be taken into consideration during medioprophylactic scheme of influence organization. As a result, it is reasonable to include into the recommended complex of therapy among the athletes with myocardosis hepatoprotectors, the preparations, which influence directly vascular system together with generally adopted means of rehabilitation. Intensive muscular activity causes direct bloodstream decrease through liver. It can become the reason for hepatic cells hypoxia. Damaged hepatic cells are more susceptible to hypoxia, than normal ones. Blood flow decrease in liver during the physical load can lead to severe necrotic tissues injury in liver, if there are some changes in liver parenchima. That is why it is important to control the state of liver at all stages of yearly cycle of training among athletes. Its early diagnostics is also necessary. Conclusion. A complex change of blood circulation apparatus in case of different pathological states, typical of sports-medical practice, demands practical material accumulation and activity-based research. The main aim of all scientific-research works, held in this direction is the following: early diagnostics, timely and purposeful therapy and pathology in sport effective prevention.